Influence of Cu+↔Ag+ Cationic Substitution on Electrical Properties of Ceramics Based on (Cu1-xAgx)7GeSe5I Nanopowders - Shender Iryna; Шендер Ірина; Filep Mykhailo; Філеп Михайло; Filep Mihály; Studenyak Viktor; Студеняк Віктор; Pogodin Artem; Погодін Артем; Malakhovska Tetyana; Малаховська Тетяна; Studenyak Ihor; et al. (IEEE, 2021)
Abstract. Ceramic samples on the basis of nanocrystalline powders Cu1-xAgx)7GeSe5I (x= 0, 0.25, 0.5, 0.75, 1) were made by cold pressing technique at a pressure of ~ 0.4 GPa with further annealing during 36 hours at 873 K. The size of ceramic materials crystallites is determined by the method of microstructural analysis. Investigation of electrical properties of ceramics based on (Cu1-xAgx)7GeSe5I mixed crystals were carried out by the method of impedance spectroscopy in the temperature range 293-383 K and in the frequency range from 10 Hz to 300 kHz. Analysis of Nyquist plots allowed to determine the ionic and electronic components of electrical conductivity, the temperature dependence of which in Arrhenius coordinates has a linear character, which indicates their thermoactivation mechanism. Compositional behaviour of both components of electrical conductivity (ionic and electronic) and their activation energies were estimated. Their nonlinear character is explained by both the complex process of recrystallization and Cu+↔Ag+ cationic substitution.
Contents: https://ieeexplore.ieee.org/xpl/conhome/9568388/proceeding?isnumber=9568389&sortType=vol-only-seq&pageNumber=4
Keywords: argyrodites; superionic conductors; solid solutions; nanopowders; imedance spectroscopy